To simplify the expression \( 13^{-5} \cdot 13^{-11} \) using the properties of exponents, we can use the property that states \( a^m \cdot a^n = a^{m+n} \).
So, we have:
\[ 13^{-5} \cdot 13^{-11} = 13^{-5 + (-11)} = 13^{-16} \]
Now we want to express this with positive exponents. We can do this by utilizing the property for negative exponents, which states \( a^{-n} = \frac{1}{a^n} \). Thus,
\[ 13^{-16} = \frac{1}{13^{16}} \]
Now let's analyze the answer choices:
- \( \frac{1}{26^6} \)
- \( \frac{1}{26^{16}} \)
- \( \frac{1}{13^{16}} \)
- \( 13^6 \)
The correct equivalent expression with only positive exponents is:
\[ \frac{1}{13^{16}} \]
Thus, the right answer is:
\( \frac{1}{13^{16}} \).